Optimization of a Redundant Freedom Machining Toolpath for Scroll Profile Machining - Song Gao; Zifang Hu; Huicheng Zhou; Jiejun Xie; Chenglei Zhang; Xiaohan Zhang (Machines)
The scroll disc is a critical functional component of the scroll compression mechanism, and its machining precision and quality directly impact the performance and longevity of the compressor. Current machining methods for scroll profiles face challenges in simultaneously achieving wide applicability, high precision, and high efficiency. This paper addresses issues related to unsmooth toolpaths of machine tool axes and high acceleration in the rotary axis during redundant degrees of freedom scroll profile machining. This paper proposes a toolpath optimization method for redundant axes, with optimization objectives focused on reducing the counts of directional changes in the linear axes and smoothing the trajectories of all axes. Experimental results demonstrate that the proposed method offers higher machining efficiency compared to traditional polar coordinate machining.